Long and short sleep duration and psychotic symptoms in adolescents: Findings from a cross-sectional survey of 15 786 Japanese students. (November 2020) - Morishima, Ryo; Yamasaki, Syudo; Ando, Shuntaro; Shimodera, Shinji; Ojio, Yasutaka; Okazaki, Yuji; Kasai, Kiyoto; Sasaki, Tsukasa; Nishida, Atsushi
Highlights: This study revealed the relationship between long sleep duration and increased risk of experiencing psychotic symptoms in male adolescents, which has not been shown before. Short sleep duration was also related with an increased risk of experiencing psychotic symptoms in male adolescents and female early adolescents. These relation remained even after adjusting for depressive symptoms. Abstract: Sleep problems during adolescence affect current and subsequent mental health and are associated with experiences of psychotic symptoms. Recent studies have suggested that short sleep duration increases the risk of experiencing psychotic symptoms in the general adolescent population; however, whether long sleep duration is associated with an increased risk of psychotic symptoms in adolescence remains unclear. The present study aimed to examine the relationships between long sleep duration, short sleep duration, and the risk of experiencing psychotic symptoms in adolescence. Cross-sectional survey data from 15, 786 junior and senior high school students (12- to 15-year-olds and 15- to 18-year-olds, respectively) in Japan were collected and analyzed using logistic regression analysis after controlling for covariates, including depressive symptoms. Long sleep duration was associated with a 1.6- to 2.8-fold increased risk of psychotic symptoms in male but not in female adolescents. Short sleep duration was also related with a 1.6- to 2.9-fold increased risk of experiencing psychotic symptoms, except for 15- to 18-year-old female adolescents. The present study suggested that adolescents with long and short sleep duration should be assessed for their risk of experiencing psychotic symptoms regardless of concurrent depressive symptoms.